PENGARUH MOTIVASI KERJA DAN INSENTIF TERHADAP KINERJA PEGAWAI DINAS PENDAPATAN DAERAH PROVINSI - Dwi Rahmawati (DINAMIKA: Jurnal Manajemen Akuntansi, Bisnis dan Kewirausahaan, 2019)
Research on Work Motivation and Incentives for Employee Performance at Lampung Province Regional Revenue Service. The population in this study were all employees of the Lampung Province Dispenda who gathered 177 people. The number of samples that will be used in this study are 49 employees from 177 employees in Dispenda Lampung Province. Data collection techniques in this study used questionnaires, documentation and interviews. The data analysis tool uses multiple linear regression. This research is quantitative descriptive which can also be interpreted as research that aims to test the facts and prove the relationship that supports and the variables that are supported (Istijanto, 2005: 18). The results showed the Work Motivation regarding the performance of employees in the Lampung Province Regional Revenue Service. Incentives play a role in employee performance in the Lampung Provincial Revenue Service. Work motivation and full incentives for employee performance in Lampung Province Regional Revenue Service.